Emerging and Evolving Topics in Multiple Sclerosis Pathogenesis and Treatments - La Flamme, Anne C.; Orian, Jacqueline Monique (Current Topics in Behavioral Neurosciences, 2015)
Over the past decade, we have made great advances in the field of multiple sclerosis (MS) research, and this book focuses on those advances in MS pathogenesis and treatment. While some of these advances have been through new approaches and ideas that have emerged in the last decade such as the newly identified protective role that amyloid proteins may play in MS or the use of helminths to treat autoimmune diseases, others have evolved from previous theories and ideas that have only now gained momentum and a deeper understanding such as the role of HLA or gender in MS susceptibility. This book covers these emerging and evolving topics and highlights the substantial advancements made in elucidation of the factors regulating susceptibility or disease progression, identification of new ways to monitor or predict MS pathology, and development of new strategies for treating MS.